Extent ‐ A Global Spatial Distribution Measure to Estimate Progression and Demonstrate Treatment Effect in Flortaucipir Scans. (20th December 2022) - Kotari, Vikas; Southekal, Sudeepti; Kennedy, Ian Andrew; Morris, Amanda; Pontecorvo, Michael J.
Abstract: Background: We previously reported that donanemab slows global and regional increase in flortaucipir standardized uptake value ratios (SUVRs) 1 . In addition to SUVR, a method to estimate spatial distribution of flortaucipir (FTP) uptake might provide valuable and complementary information. Here, we apply the previously developed Extent method to estimate the spread of FTP uptake in PET images and present comparisons against neocortical SUVR for the measurement of treatment effect in the TRAILBLAZER‐ALZ trial. We performed vertex‐wise statistical comparisons. Method: Subjects in the phase 2 TRAILBLAZER‐ALZ study completed FTP and florbetapir PET scans and MRIs at baseline and 18‐months. Flortaucipir images were processed using standard techniques 2 and normalized to the cerebellum crustaneous reference region 3 . Each FTP image was converted to a z‐score image relative to sixteen young cognitively normal (YCN) subjects. Clusters with z‐scores smaller than a false discovery rate corrected p‐value of 0.01 were retained within a predefined neocortical mask. The neocortical mask and thresholds were selected based on previous data to maximize signal to noise ratio in 18‐month change of mild AD subjects. Extent is the ratio of voxels in this predefined mask that have abnormally elevated tau, defined as at least 2.32 * SD above the mean of YCNs (values range between 0‐1). The primary outcome was 18‐month change in Extent and MUBADA 2 SUVR between placebos and donanemab treated subjects. We performed vertex‐wise group comparisons to capture the differences in tau burden. Result: Both Extent and MUBADA showed significant difference between treated and placebo subjects (Figure 1). The 18‐month change (SUVR and Extent) surface maps of the treated and placebo groups show larger spread of FTP in the superior, middle and medial orbito‐frontal regions (Figure 2 & 3). The difference and p‐value maps show clusters of vertices in the inferior temporal, parahippocampal, supramarginal, middle, medial and superior frontal regions as being significantly different. Conclusion: Subjects treated with donanemab have significantly lesser flortaucipir distribution by Extent compared to placebo, and differences in surface maps of intensity and spread of FTP. Clusters in temporal, parietal, and frontal regions were significantly different. In addition to intensity differences, spatial distribution was different between treatment groups.